From open-access to individual quotas: Disentangling the effects of policy reform and environmental changes in the Norwegian coastal cod fishery - Florian Diekert; Kristen Lund; Tore Schweder (University of Oslo, Department of Economics, 2014)
Understanding the effect of introducing property rights to natural resources is central in economics, but empirical analysis is frustrated by the complexity of socioecological systems. We construct a detailed bio-economic model of the Norwegian coastal cod fishery, which was closed after 1989, to isolate the effect of environmental variability. We project stock and harvest forward in the counterfactual scenario of no intervention, showing that the policy had only a small positive impact on stock biomass, but a pronounced positive effect on profits. The main driver, uncovered by index-number decomposition, is savings in fuel and labor costs.
Keywords: C43; D23; Q22; Q28; 330; Open access; Property rights; Quasi-experiment; Counterfactual control; Bio-economic modeling; Productivity; North-East Arctic cod